Cyclophosphamide Increases Lactobacillus in the Intestinal Microbiota in Chickens - Dany Mesa (American Society for Microbiology, 2020)
ABSTRACT Recent data in humans indicate that immunosuppression is correlated with shifts in the intestinal microbiota. However, the relationship between immunosuppression and intestinal microbiota has not been studied in chickens. Thus, we investigated the correlations between immune cells and intestinal microbiota by massive parallel sequencing of the 16S rRNA bacterial gene in chickens immunosuppressed with cyclophosphamide. The results showed correlations between peripheral immune cells and intestinal microbiota. Surprisingly, an increase in the abundance of intestinal Lactobacillus in the immunosuppressed chickens was observed. These birds also had low intestinal IgA antibody levels among other alterations in the microbiota. These shifts indicate a role of the immunity system in controlling the microbiota of birds. IMPORTANCE Poultry production is a very intensive industry. Due to the substantial number of animals being raised by any one producer, even small variations in productivity lead to important economical outcomes. The intestinal microbiota of birds is under intense scrutiny by the immune system. Therefore, it is a factor that can influence the states of health and disease of the host. The body of knowledge on the interactions between these systems is gradually bringing practical guidance for poultry production.